(untitled) (The Pakistan Development Review, 2001)
Rising from the debris of the World War-II and also the devastations caused by the great depression of 1930s, the Bretton Woods twins—international monetary fund (IMF) and the world bank; rather the world bank group1—have over the years emerged as important players of the international financial arena. They are the major component of international financial architecture in addressing global macro and financial stability. The Bank together with the regional multi-lateral development banks (MDBs), such as the Asian Development Bank (ADB) for the Asian and the Pacific region, is making its contribution in building necessary infrastructure needed to initiate and support the development process, the recent reduced emphasis on such projects notwithstanding.